Efficient Thiolation of Alcohols Catalyzed by Long Chained Acid‐Functionalized Ionic Liquids under Mild Conditions. Issue 19 (7th May 2019) - Miao, Chengxia; Zhuang, Hongfeng; Wen, Yating; Han, Feng; Yang, Qing‐Feng; Yang, Lei; Li, Zhen; Xia, Chungu
Abstract : Thioethers as important building blocks have been usually found in organic synthesis. Herein, a series of long chained acid‐functionalized ionic liquids derived from pyrrolidine were applied for the thiolation of alcohols to synthesize different compounds containing thioether structures. This kind of ionic liquids exhibited higher efficiency than general ionic liquids based on imidazole, providing up to 99 % yield with [BsCtP][OTf] as the catalyst at room temperature for 0.25 h. The results indicated that the activities of the ionic liquids have relationship with the side chain length of ionic liquids based on pyrrolidine, anions and cations. The catalytic system had wide substrate scope and was applicable for the reaction of aromatic primary and secondary alcohols and thiols including aliphatic and aromatic thiols, benzothiazole‐2‐thiols and benzooxazole‐2‐thiols. Besides, there was no obvious change in activity of the catalyst after six runs. Thus, the catalytic system exhibited good recyclability. Additionally, carbocations should be the key intermediate and several functionalized groups of the ionic liquids have synergetic effect for the thiolation. Abstract : Long chained and SO3 H‐functionalized ionic liquids derived from pyrrolidine were employed as metal‐free, efficient and recyclable catalyst for thiolation of alcohols with several kinds of thiols, providing up to 99 % yield within 0.25 h at room temperature.